(untitled) (Global Journals of Research in Engineering, 2022)
This paper focuses on combining resistivity and pressure measurements to determine the effectiveness of foam as a mobility control method It presents a theoretical framework to describe the expected resistivity changes during CO2-foam displacements With this objective we first provide equations to estimate the resistivity for CO2-foam systems and then utilize two distinct foam models to quantify these effects Using analytical solutions based on the fractional flow theory we present resistivity and mobility distributions for ideal and non-ideal reservoir displacement scenarios Additionally assuming pressure measurements only we examine the inter-dependency between various foam parameters Our results suggest that the combination of pressure and resistivity measurements in time-lapse mode could be deployed as an effective monitoring tool in field applications of the CO2 foam processes The proposed method is novel as it could be employed to predict under-performing CO2-foam floods and improve oil recovery and CO2 storage